Synthesis and antimicrobial activity of beta-lactam-bile acid conjugates linked via triazole - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Chavan, Pradnya S.; Deshpande, Mukund V. (Bioorganic & Medicinal Chemistry Letters, 2008)
Synthesis of novel 1,2,3-triazole-linked beta-lactam-bile acid conjugates 17-24 using 1,3-dipolar cycloaddition reaction of azido beta-lactam and terminal alkyne of bile acids in the presence of Cu( I) catalyst ( click chemistry) have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and moderate antibacterial activity against all the tested strains. (c) 2008 Elsevier Ltd. All rights reserved.

Antifungal activity and mechanism of action of carvacrol and thymol against vineyard and wine spoilage yeasts - Chavan, Pradnya S.; Tupe, Santosh G. (Food Control, 2014)
Antimicrobial activity of carvacrol and thymol against natural yeast flora of the grapes and yeasts known to cause wine spoilage was examined. Carvacrol and thymol exhibited comparable or better antifungal activity than potassium metabisulphite, commercially used wine preservative, against the natural yeast flora and spoilage yeasts. The antifungal activity for both the compounds was better at pH 3.5 than pH 6.5. Addition of carvacrol and thymol (64 mu g/mL) in red wine resulted in inhibition of growth of the spoilage yeasts. Carvacrol and thymol exerted their antimicrobial action through membrane damage, leakage of cytoplasmic content and ergosterol depletion. In conclusion, carvacrol and thymol holds promise as a potential natural preservative for the control of wine spoilage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Carvacrol; Thymol; Wine spoilage